Financial Decision of Tunisian Firms in the Context of Market Timing Theory - Ramzi Drissi; Tarek Ghazouani; Assaad Ghazouani (International Journal of Economics and Financial Issues, 2013)
This work focuses on the study of the determinants of capital structure in the context of the "Market Timing" theory in a sample of 20 Tunisian firms listed on the Tunis Stock Exchange during the period 2004-2010. The empirical analysis shows that the results are inconclusive regarding the relevance of certain variables from this theoretical framework due to various reasons including market inefficiency. We can also invoke the behavioral dimension of Tunisian companies insofar as direct finance is not often the preferred alternative by the agents as well as to those in need financing capacity.